Matemática atuarial como ferramenta de apoio ao ensino da matemática financeira - Garcia, Tiago Minucelli [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
O presente trabalho propõe a utilização da Matemática Atuarial como apoio ao ensino da Matemática Financeira, envolvendo, ainda, alguns conceitos de Probabilidade. Para isso, é proposta uma simples aplicação que se vale de planilhas eletrônicas, a fim de abordar, no cotidiano do aluno, temas como Seguro de Vida e Previdência Complementar. A base teórica está fundamentada principalmente em Azevedo (2005) e Carvalho (2015), além dos PCNs, PCNEM e BNCC, os quais propõem, como sentido do aprendizado, que o conteúdo ensinado seja útil à vida e ao trabalho, além de possibilitar ao aluno uma leitura e interpretação da realidade, a fim de desenvolver suas capacidades. Após a explanação teórica das noções da Matemática Atuarial, como resultado, o capítulo final do trabalho dispõe de duas planilhas de fácil confecção para o cálculo de previdência complementar e seguro de vida, as quais podem ser aplicadas pelo professor durante a exposição do conteúdo.

The present work proposes the use of Actuarial Mathematics as a support to the teaching of Financial Mathematics, involving some concepts of Probability. Therefore, a simple application is proposed which uses electronic spreadsheets, in order to approach, in the student’s daily routine, subjects such as Life Insurance and Supplementary Pension. The theoretical framework is mainly based on Azevedo (2005) and Carvalho (2015), besides to PCNs, PCNEM and BNCC, which propose, as a sense of learning, that the content taught is useful to life and work, as well as enabling the student a reading and interpretation of reality in order to develop their capabilities. After the theoretical explanation of the notions of Actuarial Mathematics, as a result, the final chapter of this paper has two spreadsheets for calculation of supplementary pension and life insurance, which can be easily prepared and applied by the teacher during the content exposition.
Actuarial mathematics as a support to the teaching of financial mathematics
Keywords: Matemática atuarial; Matemática financeira; Planilhas eletrônicas; Actuarial mathematic; Financial mathematic; Electronic spreadsheets